Anti-Corruption Education, Is It Important? - Syahputra, Yesaya Brian; Theotama, Gracella; Hapsari, Aprina Nugrahesthy Sulistya (Association of Certified Fraud Examiners Indonesia Chapter, 2024)
The endless phenomenon of corruption proves that the level of public awareness of corruption is still low and anti-corruption education is needed as early as possible to mitigate the occurrence of corrupt practices in Indonesia, including at the higher education level. The urgency of implementing anti-corruption education also needs to begin with individual awareness of the importance of anti-corruption education. This is a preliminary study that aims to measure students’ perception of anti-corruption education in higher education. This study conducted a survey of several students in all faculties at Universitas Kristen Satya Wacana (UKSW) to see the understanding and the importance of anti-corruption education in the university. The result showed that most of UKSW students understand about corruption and any matters related. The students mostly agree that the role of anticorruption education is very important in efforts to prevent corruption. Furthermore, the learning curriculum at UKSW has accommodated anti-corruption education even though it is not yet explicit and specific.